ANALISIS SWOT MENINGKATKAN PENJUALAN PADA DEALER SURYA INTI PUTRA SIDOARJO - Putra Adi Wiranca; Menur Kusumaningtyas (PUTRA JAWA PUBLISHER, 2024)
This article aims to conduct a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis in order to formulate a sales improvement strategy at Surya Inti Putra Dealer in Sidoarjo. Through SWOT analysis, we identified various internal and external factors that affect the performance of the dealership. The strengths of the dealership include good reputation, strategic location, complete product availability, adequate after-sales service, and competent human resources. Weaknesses identified include less effective marketing, less competitive pricing, limited information systems, and lack of digital services. Opportunities that can be capitalized on are the growth of the automotive market, development of digital technology, strategic partnerships, and product diversification. Threats include intense competition, regulatory changes, economic crisis, and changing consumer preferences. Based on this analysis, recommended strategies include optimizing digital marketing, promotion and discount programs, improving customer service, developing human resources, strategic partnerships, and product diversification. The implementation of these strategies is expected to increase sales and strengthen Surya Inti Putra Dealer's position in the Sidoarjo automotive market.